Optimalisasi Branding Awareness pada Kelompok Petani Jamur dalam Peningkatan Kualitas Produk - Syarifudin, Achmad; Wardhana, Indra J. K.; Ummah, Kuntum C.; Purwanto, Edy (Jurnal Solutif: Jurnal Pengabdian Masyarakat, 2025)
Branding awareness is a very important part of efforts to improve and recognize products. As a step and strategic to provide knowledge about branding awareness to the community, the sociology study program of Trunojoyo University Madura held a socialization program for mushroom farmers who are under the auspices of the Karya Sejahtera Farmer Group association located in Singosari District, Malang Regency, East Java. This socialization was held as a form of community service in the realm of the tri dharma of higher education. The problems found include farmers not knowing about what branding awareness is so that the products produced are not yet of legal standard. The results of the socialization given to farmers include increasing farmers' awareness of the brand of products they sell, as well as gaining new knowledge about the concept of branding awareness that they must master. Through the results of the socialization, farmers can improve the quality of their products and introduce processed products to the wider community.